KAJIAN LITERATUR: PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEAKTIFAN DAN HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Ramadhini, Nurlayalia; Sry Amalinda; Najmi Nazarni Khalisa; Nayna Putri; Ahmad Suriansyah; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the Student Teams Achievement Divisions (STAD) cooperative learning model on students’ activeness and learning outcomes in the IPAS subject at the elementary school level through a literature review approach. Data were obtained from various relevant studies on the implementation of STAD in IPAS learning. The findings indicate that STAD effectively enhances student activeness through heterogeneous group work, peer tutoring, and individual evaluation, which encourage participation and learning responsibility. Moreover, STAD improves learning outcomes, critical thinking skills, and student motivation. However, its implementation requires teachers’ readiness in managing time, group dynamics, and consistent assessment. Overall, the review confirms that STAD is a viable instructional model to improve the quality of IPAS learning in elementary schools.